Unmasked lost music for the 1613 Palatine wedding masques - Duffin, Ross W. 1951- (Oxford University Press, 2025)
The 1613 marriage of Princess Elizabeth of England to Count Palatine was one of the most spectacular events of King James's court, lavishly celebrated with banquets, tournaments, fireworks, and most notably, with masques-extravagant entertainments with elaborate sets, costumes, dancing, and songs. Although the masque lyrics were all printed with the dialogue in 1613, music survives for only one song. In 'Unmasked', author Ross W. Duffin reconstructs music for the three wedding masques of Thomas Campion, George Chapman, and Francis Beaumont, revealing through close reading that the songs are partsongs sung by an ensemble, rather than an accompanied solo singer. His reconstruction enables complete performance of the masques for the first time in four centuries
Includes bibliographical references and index
Keywords: Frederick / I / King of Bohemia / 1596-1632 / Marriage; Elizabeth / Queen, consort of Frederick I, King of Bohemia / 1596-1662 / Marriage; Music / ukslc; Music / thema; Masques with music / 17th century / History and criticism; Masques with music / Librettos; Wedding music / England / 17th century / History and criticism; Dance / England / History / 17th century; Masques, English / History and criticism; Masques, French / History and criticism; Royal weddings / England / 17th century